2020
DOI: 10.4171/jca/46
|View full text |Cite
|
Sign up to set email alerts
|

Keys and Demazure crystals for Kac–Moody algebras

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…This is in parallel to the models in [16,20] with Gelfand-Tsetlin patterns and reverse semistandard tableaux because we can only use one particular ordering of the spectral parameters. We conjecture that our key map agrees with the representation-theoretic description coming from the Kashiwara crystal structure [22,40] described in [38], the key map on Kashiwara-Nakashima (KN) tableaux [41] given in [71], and with the crystal structure defined recently on King tableaux by Lee [56]. A salient ingredient is a weight-preserving bijection from reverse King (respectively, Sundaram) tableaux to regular King (respectively, Sundaram) tableaux.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…This is in parallel to the models in [16,20] with Gelfand-Tsetlin patterns and reverse semistandard tableaux because we can only use one particular ordering of the spectral parameters. We conjecture that our key map agrees with the representation-theoretic description coming from the Kashiwara crystal structure [22,40] described in [38], the key map on Kashiwara-Nakashima (KN) tableaux [41] given in [71], and with the crystal structure defined recently on King tableaux by Lee [56]. A salient ingredient is a weight-preserving bijection from reverse King (respectively, Sundaram) tableaux to regular King (respectively, Sundaram) tableaux.…”
supporting
confidence: 76%
“…Additionally, applying the tableau-switching algorithm from is a crystal isomorphism with the crystal structure on given by Lee [56]. Moreover, the composition of applying the tableau-switching algorithm to interchange for all i , replacing entry-wise, and applying the Sheats bijection is a crystal isomorphism on the corresponding crystal atoms that sends to the key map defined in [38, 71].…”
Section: Key Algorithm and Proctor Patternsmentioning
confidence: 99%
“…In those questions, Azenhas identified some type C n Kashiwara-Nakashima tableaux as key tableaux, which match our identification, but it lacks a construction of the right key map, thus lacking a proof of the combinatorial description of type C Demazure characters. Note also that, during the preparation of this paper, Jacon and Lecouvey informed us about their paper [12], where they find the same key in type C, but their approach is different from ours.…”
Section: Introductionmentioning
confidence: 71%
“…For a complete overview in type A, see [3] and the references therein. In type C n , the symplectic key tableaux are characterized in [2,14,15,6]. Using the Sheats symplectic jeu de taquin, a right key map is given, in [14,15,6], to send a Kashiwara-Nakashima (KN) tableau T to its right key tableau K + (T), that detects the Demazure atom crystal which contains T. They are also computed in the type C n alcove path model [11], as well as for reverse King tableau using the colored five vertex model [4].…”
Section: Introductionmentioning
confidence: 99%
“…Jacon and Lecouvey [6] have suggested that Willis' method should be adaptable to type C n . Motivated by Willis' direct inspection [17], we create an alternative algorithm, based on the direct inspection of a KN tableau, for the symplectic right key map, that does not use the symplectic jeu de taquin.…”
Section: Introductionmentioning
confidence: 99%